Saudi women, present and future | المرأة السعودية الحاضر والمستقبل - Al Khashil | آل خشيل, Maha | مها; Al-Rakaf | الركف, Nada | ندى; Al-Hazza | الهزاع, Hanan | حنان (Princess Nourah bint Abdul Rahman University | جامعة الأميرة نورة بنت عبد الرحمن, 2024)
Art is one of the ways Saudi women express their issues. Women themselves were and still are a source Inspiration in practicing visual arts of all kinds, its giving and its role in society, the beauty of its spirit And her love of beauty has made her an icon for many artists in the Kingdom of Saudi Arabia for a long time Pioneers and to this day, how could she not be a caring mother, a generous sister, a loyal wife, and a virtuous daughter? | ُيعد الفن أحد طرق تعبير المرأة السعودية عن قضاياها. والمرأة بحد ذاتها كانت ولا زالت مصدر إلهام في ممارسة الفنون البصرية بمختلف أنواعها، عطاؤها ودورها في المجتمع، جمال روحها وحبها للجمال، كل ذلك جعلها أيقونة للكثير من الفنانين في المملكة العربية السعودية، منذ زمن الرواد وحتى يومنا هذا، كيف لا وهي الأم الحنون، والأخت المعطاء، والزوجة الوفية، والابنة البارة